The Effect of Government Accounting Systems and Human Resource Competencies on the Quality of Financial Reports in Minahasa District - Florence Moroki; Debora Prisilia Lengkong; Miryam P Lonto (Universitas Sam Ratulangi, 2024)
This study aims to determine how the Effect of Government Accounting System on the Quality of Financial Statements in Minahasa Regency; and How the Effect of Human Resource Competence on the Quality of Financial Statements in Minahasa Regency. The data collection technique is a questionnaire, and this research is quantitative research. The research results are as follows. First, Identify the effect of the Government Accounting System on the quality of financial reports in Minahasa Regency. Second, Identify the effect of Human Resource Competence on the quality of financial reports in Minahasa Regency.This research uses quantitative research using the survey method. Data were collected using questionnaires distributed to sub-district offices in Minahasa Regency using purposive sampling techniques. Data collection techniques used observation, interviews and documentation techniques and the data analysis technique used was the SPSS 29 data processing software application program.The conclusion of this study is that the Government Accounting System has a positive effect on the Quality of Financial Statements. Keywords : Government, Accounting, System, Financial, Reports.